2018
DOI: 10.1021/acs.iecr.8b04904
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Thermodynamic Complexity Constants and Speciation for Multicomplexing Electrolytes within the Mean Spherical Approximation Model

Abstract: It has been shown in previous work that the determination of speciation in aqueous solutions containing self-complexing electrolytes requires caution as regards the thermodynamic model used to estimate the activity coefficients of the solute species, and the complexity constants values, which seem uncertain if not irrelevant in some cases. This topic was studied using a simple molecular model based on the mean spherical approximation (MSA) theory. In the present work, the case of aqueous ternary mixtures with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…For these solutions, not only ion pairing is really strong but also there is evidence of the presence of ion triplets and higher aggregates. 53,57 Except for CdCl 2 and CdI 2 , the predicted molar conductivities are in acceptable agreement with the experimental data. It also should be noted that for most of the 2:1 electrolytes, the RAAD % of model 1 and model 2 is less than other models.…”
Section: Evaluation Of Thesupporting
confidence: 69%
“…For these solutions, not only ion pairing is really strong but also there is evidence of the presence of ion triplets and higher aggregates. 53,57 Except for CdCl 2 and CdI 2 , the predicted molar conductivities are in acceptable agreement with the experimental data. It also should be noted that for most of the 2:1 electrolytes, the RAAD % of model 1 and model 2 is less than other models.…”
Section: Evaluation Of Thesupporting
confidence: 69%
“…The results are compared with those from the Davies equation. For this purpose, the program “CHEAQS Next” (refs and ) and FORTRAN programs implemented in refs and were employed. The two were cross-checked against each other.…”
Section: Resultsmentioning
confidence: 99%
“…For the calculations mentioned above, we used CHEAQS Next software. , Detailed computational procedures are elaborated on by Simonin et al. , …”
Section: Discussionmentioning
confidence: 99%
“…63,64 For the calculations mentioned above, we used CHEAQS Next software. 65,66 Detailed computational procedures are elaborated on by Simonin et al 62,67 As indicated in the literature 62 concerning cadmium halides, the maximum number of anions in the complex, denoted as n, is set to 4. The cumulative complex formation constant was obtained from the NIST database.…”
Section: Electrical Conductivity Of Electrolyte Solutions Forming Ionmentioning
confidence: 99%